1985
DOI: 10.1093/infdis/152.6.1107
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Resistance to Trimethoprim-Sulfamethoxazole Among Isolates of Escherichia coli in Developing Countries

Abstract: Resistance of Escherichia coli to trimethoprim (TMP)-sulfamethoxazole remains at 3%-8% at many medical centers within the United States. In this study a 44% resistance rate was observed among E. coli isolated at a pediatric hospital in Santiago, Chile, and a 40% resistance rate at a general teaching hospital in Bangkok, Thailand. Most isolates were from urinary tract infections and showed high-level resistance (minimal inhibitory concentration of TMP greater than 1,000 micrograms/ml). Nineteen of 35 isolates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
1
4

Year Published

1988
1988
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(65 citation statements)
references
References 21 publications
3
57
1
4
Order By: Relevance
“…Young et al (1986) found 58 different plasmid types associated with trimethoprim resistance in isolates from south India. Murray et al (1985) found plasmid sizes ranging from 42 to 80 MDa associated with trimethoprim resistance in Chilean isolates. In our study, plasmids of molecular weight 62 MDa occurred most frequently, and were associated with different resistance patterns.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Young et al (1986) found 58 different plasmid types associated with trimethoprim resistance in isolates from south India. Murray et al (1985) found plasmid sizes ranging from 42 to 80 MDa associated with trimethoprim resistance in Chilean isolates. In our study, plasmids of molecular weight 62 MDa occurred most frequently, and were associated with different resistance patterns.…”
Section: Resultsmentioning
confidence: 93%
“…Considerable attention has been paid to the indiscriminate use of antibiotics (Murray et al 1985;Koh, 1986;Burke & Levy, 1985). This is particularly the case in the management of diarrhoeal diseases despite W.H.O.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trimethoprim (TMP) either alone or in combination with sulfamethoxazole (cotrimoxazole) is commonly used as standard therapy for urinary tract infections, and increased resistance to both agents have been reported to occur in isolates of Escherichia coli in different parts of the world [1][2][3][4]. The introduction of newer alternative antimicrobial agents have also resulted in rapidly developing resistance which threatens the usefulness of these agents [5].…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries, however, resistance is a growing problem, with high levels being reported in Africa, South America and Asia amongst enterobacteria [5][6][7], including Salmonella spp. [8,9] and Shigella spp. [10][11][12].…”
Section: Introductionmentioning
confidence: 99%